Cambodia : World Bank Country-Level Engagement on Governance and Anticorruption - Girishankar, Navin; DeGroot, David; Desai, Raj; Stout, Susan; Wescott, Clay (World Bank, Washington, DC, 2017)
Cambodia is one of the world's most open economies, sustaining high levels of growth in an environment of relatively weak governance. Emerging from a legacy of genocide and civil conflict, the country has sought to address human and social capital deficits across sectors, weaknesses in public finance, and corruption. Despite improvements in access to basic services, governance constraints persist and may threaten gains from economic integration. Over the 2004-10 period, the Bank's engagement on Governance and Anticorruption (GAC) issues in Cambodia was not defined by a single, overarching priority or entry point (such as core public sector management, natural resource management, or service delivery). Rather, the Bank was opportunistic, opting to support the government's GAC efforts across multiple sectors and institutions. The relevance of this opportunistic approach is judged to be moderately relevant. The Bank's objectives on public financial management (PFM) were highly relevant given Cambodia's nontransparent and weak public expenditure management and limited capacity. The Bank's response to sectoral governance weaknesses such as red tape, inefficiencies, and other forms of rent-seeking in customs is rated modest given the need for the government to implement its World Trade Organization commitments. The Bank's project level engagement is rated as moderately relevant. As a basis for reinstating suspended projects, portfolio-wide measures included the use of an Independent Procurement Agency (IPA) for the International Development Association (IDA) procurements, and the implementation of Good Governance Frameworks (GGF) for all IDA projects.